Passionately demanding: Work passion’s role in the relationship between work demands and affective well-being at work - Cabrita, Catarina; Duarte, Ana Patrícia (Frontiers in Psychology, 2023)
In a world marked by exponential change, work demands are intensifying and becoming increasingly prominent in organizations’ reality. Work demands are stressors for the employees who must deal with these requests as they bring with them costs. Promoting these workers’ well-being at work is important as their level of comfort is closely related to how they will behave in the workplace. In this context, work passion is a fundamental factor in employees’ daily motivation to work well. This study tested a new approach to work demands, distinguishing between challenges and obstacles, exploring how they influence affective well-being at work when work passion is part of the equation. Individual workers also participate in how demands are formulated, which affects their level of well-being at the workplace. Data were collected with an online questionnaire administered to a sample of 515 participants who had been working in the same organization for at least six months. The results of multiple regression analysis show that the way demands are revealed influences what kind of work passion predominates and thus how much workers’ well-being at work is altered. Harmonious passion emerges as a personal resource that has the power to prevent negative affective states related to work from developing, while obsessive passion ends up putting even more demands on employees and having a stronger negative association with their affective well-being in the workplace.